Implementasi Raised Bed Berbasis Limbah Organik pada Pertanian Perkotaan untuk Mendukung Food Coping Strategy: Implementation of Raised Bed Based on Organic Waste in Urban Agriculture to Support Food Coping Strategy - Wanti Mindari; Mirza Ramadhani; Oentari Prilaningrum Sutanto; Melinda Trisya Yulianto; Qonita Mumtazia Kamilah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Urban farming has emerged as one of the solutions to strengthen food security, improve environmental quality, and provide economic benefits in urban areas. One commonly applied method is the raised bed system, which optimizes the use of limited land and enhances the efficiency of soil media management. However, farmer groups often face challenges in managing organic waste and optimizing growing media in restricted spaces. This community service program was implemented in collaboration with the Minasari Farmers Group located on Jemursari XIX Street, Jemur Wonosari Sub-district, Wonocolo District, Surabaya, involving 23 members. The stages of activities included site survey and green space landscape design, construction of raised beds, application of Hugelkultur techniques using organic waste (banana trunks, twigs, and other biomass materials), delivery of crop cultivation training, and program evaluation. The results showed that the application of Hugelkultur-based raised beds improved the quality of planting media, expanded opportunities for vegetable and herbal crop cultivation, and supported circular economy principles (3R: Reduce, Reuse, Recycle). Through this program, the Minasari Farmers Group is expected to become a model for productive, aesthetically pleasing, and sustainable urban farming in Surabaya.